IMPROVEMENT OF EFFICIENCY OF USE OF LIQUID-GLASS MIXTURES. OVERVIEW INFORMATION. PART 1. MODIFICATION - A. N. Krutilin; Yu. Yu. Huminski; O. A. Rusevitch; L. V. Kulbitskaya (Литьë и металлургия)
The basic directions of improvement of properties of silicate binders and mixtures on their basis are generalized. Organic and inorganic additives for liquid-glass mixtures and autoclave modification are considered. A huge number of various additives proposed to improve the knockout rate of liquid-glass mixtures is due to the complexity of the processes occurring in the mixtures at high-temperature exposure. In order to obtain the optimal structure, it is necessary to ensure the presence in the silicate solution of colloidal particles of liquid glass and active functional groups of a polymeric modifier capable of interacting with this surface.